2, 3, 7, 8-tetrachloro-dibenzo-p-dioxin induced testicular toxicity in rats and the protective effect of quercetin: Biochemical, histopathological and immunohistochemical studies - Mohamed SA. El-Gerbed, Ahmed M. Abu El-Saad, Abdullah Bedeer Haussein (Journal of Applied Pharmaceutical Science, 2015)
Humans and animals are most sensitive to toxicant exposure during development. Dioxin, as an endocrine disruptor, is known to impair testicular functions and fertility. The present study was carried out to investigate the effects of quercetin on TCDD-induced toxicity in the testicular tissue of rats. Forty male albino rats were randomly divided into four groups (n = 10/group). Group I represent the control group; Group II administrated TCDD (27.5 µg/kg) via gavage for four week; Group III received quercetin (20 mg/kg bw.) Via gavage before TCDD administration; Group IV received quercetin alone (20 mg/kg bw). Biochemical markers included levels of testicular malondialdehyde formation and reduced glutathione as well as monitoring the activities of testicular superoxide dismutase, catalase, glutathione peroxidase, glutathione S-transferase were studied. Also, serum hormonal profiles of luteinizing hormone and testosterone were reported. Our results show that administration of TCDD induces testicular damage concerning oxidative stress parameters, serum hormone level and sperm parameters. In addition, the microscopic structures of the testis, including histological and immunohistochemical studies were evaluated. Exposure to TCDD induces histopathological changes in rats testis including degeneration of seminiferous tubules, tubular necrosis, intratubular vacuolization, widened lumen and deshaped germ cells. Marked increase of apoptotic activity was observed. Also, our results clearly demonstrate the ameliorative potential of quercetin in dioxin induced testicular damage.
Keywords: TCD, Quercetin, Testis,Oxidative stress.